Detection of staphylococcal enterotoxins by enzyme-linked immunosorbent assays and radioimmunoassays: comparison of monoclonal and polyclonal antibody systems. - Thompson, N E (1986)
Murine monoclonal antibodies reactive with at least one of the serological types of staphylococcal enterotoxin were examined for use in assay systems for the detection of enterotoxin at the level of 1.0 ng of enterotoxin per ml. An antibody sandwich enzyme-linked immunosorbent assay was devised for each toxin type by identifying an effective antibody pair. One antibody (the coating antibody) was coated onto a polystyrene plate and removed the enterotoxin from the test solution; the second antibody (the probing antibody) was conjugated to horseradish peroxidase and detected the captured toxin. Enterotoxins A and E could be detected in the same system by the use of cross-reacting monoclonal antibodies. All subtypes of enterotoxin C could be detected in one assay system. Two effective systems were described for each of types B and D. Each of these systems, when compared with the homologous enterotoxin-specific polyclonal rabbit antibody systems, was found to compare favorably. The monoclonal enzyme-linked immunosorbent assay systems for the detection of enterotoxins A and C2 were examined for a variety of food extracts; no abnormal interference could be detected from these extracts. The monoclonal antibody systems were also compared with the homologous enterotoxin-specific polyclonal serum for the detection of enterotoxin by the competitive radioimmunoassay (RIA). Single monoclonal antibodies generally did not perform as well in the RIA as did the homologous toxin-specific polyclonal serum. However, pools of monoclonal antibodies were prepared that approached the sensitivity and precision of the polyclonal system for the detection of each toxin by the RIA.